Моделі для оцінки ризику експлуатації системи радіоуправління безпілотним літальним апаратом - Мащак, Андрій Володимирович (Національний університет "Львівська політехніка", 2016)
В дисертаційні роботі представлено розв’язання науково-прикладної задачі зменшення рівня ризику експлуатації навігаційно-обчислювальної системи безпілотного літального апарата (БпЛА) за рахунок обґрунтованого підвищення надійності складових, найбільш критичних з точки зору ризику експлуатації системи. Розв’язання поставленої задачі полягало в розробці методики визначення кількісного показника ризику навігаційно-обчислювальної системи БпЛА, а саме ймовірності виникнення мінімального січення, без побудови дерева відмов. Методика дозволяє вирішувати задачі зменшення рівня ризику експлуатації навігаційно-обчислювальної системи БпЛА на етапі системотехнічного проектування. Для методики оцінки рівня ризику експлуатації навігаційно-обчислювальної системи БпЛА розроблено математичні моделі навігаційної та обчислювальної підсистем з деталізованим представленням стану критичної відмови. Розроблено алгоритм та прототип програмного засобу, в основу якого покладено запропоновану методику оцінки рівня ризику експлуатації навігаційно-обчислювальної системи. Програмний засіб автоматизує процес отримання кількісного показника ризику, в якому враховуються: відмовостійкі конфігурації підсистем; відмови апаратних засобів; збої програмних засобів; належність певної частини відмов до двох і більше мінімальних січень; вплив ненадійності приймача сигналу від супутникової навігаційної системи; вплив ненадійності приймача системи зв’язку з оператором. Для візуалізації причин та наслідків аварійних ситуацій програмний засіб дозволяє автоматизовано побудувати дерево відмов на основі мінімальних січень. В диссертационные работе представлено решение научно-прикладной задачи уменьшения уровня риска эксплуатации навигационно-вычислительной системы беспилотного летательного аппарата (БпЛА) за счет обоснованного повышения надежности составляющих, наиболее критичных с точки зрения риска эксплуатации. Решение поставленной задачи заключалась в разработке методики определения количественного показателя риска эксплуатации навигационно-вычислительной системы БПЛА, а именно вероятности возникновения минимального сечения, без построения дерева отказов. Методика позволяет решать задачи уменьшения уровня риска эксплуатации навигационно-вычислительной системы БпЛА на этапе системотехнического проектирования. Для методики оценки уровня риска эксплуатации навигационно-вычислительной системы БПЛА разработаны математические модели навигационной и вычислительной подсистем с детализированным представлением состояния критического отказа. Разработан алгоритм и прототип программного средства, в основу которого положена предложенная методика оценки уровня риска эксплуатации навигационно-вычислительной системы. Программное средство автоматизирует процесс получения количественного показателя риска, в котором учитываются: отказоустойчивые конфигурации подсистем; отказ аппаратных средств; сбои программных средств; принадлежность определенной части отказов к двум и более минимальным сечениям; влияние ненадежности приемника сигнала от спутниковой навигационной системы; влияние ненадежности приемника системы связи с оператором. Для визуализации причин и последствий аварийных ситуаций программное средство позволяет автоматизировано построить дерево отказов на основе минимальных сечений. In this work were solved a scientific and applied task of increasing the degree of risk assessment adequacy of reliability components models of unmanned aerial vehicles (UAV) computing-navigational onboard system. This task is solved by reasoned reliability improving of the most critical in terms of safety UAV computing-navigational subsystem modules and subsystems. Solving this problem was based on developing of a methodology for quantitative determining the risk index of computer and navigation subsystem of UAV computing-navigational onboard system. Namely this risk index is a minimal cut sets which are determined without fault tree building. Proposed methodology allows to meet the challenges of exploitation risk level reducing of UAV computing-navigational system in the design phase stage of UAV development. This is achieved by assessing the exploitation risk of UAV modules different variants and configuration options with taking into account the cost of its realization. For the methodology of assessing the exploitation risk level of UAV computing-navigational system were developed a reliability computing subsystem model and navigation subsystem model. These subsystems are the main part of UAV radio system. Models are developed with a high detailed representation of the critical fail state. This high detailed representation of the critical fail state gives opportunity to determine the faults of separate modules which causes to fail of whole UAV computing-navigational system. Also the algorithm and prototype software tool is developed. This software tool is based on the proposed methodology for assessing the exploitation risk level of UAV computing-navigational system. Software tool automates the processes of obtaining quantitative risk index. Obtained quantitative risk index takes into account: subsystems fault-tolerant configurations; hardware failures; software failures; affiliation of certain failure to two or more minimal cut sets; reliability of satellite navigation systems signal receiver; reliability of operator commands receiver. Also to visualize the causes and consequences of fails the proposed software tool allows to build in automated mode the fault tree which is based on obtained minimal cut sets. Based on developed algorithm and models is made a possibility to make a quick model rebuild for risk assessment.
Модели для оценки риска эксплуатации системы радиоуправления беспилотным летательным аппаратом
Models for risk assessment of unmanned aerial vehicle radiosystem
Keywords: безпілотний літальний апарат; навігаційно-обчислювальна система; оцінка ризику експлуатації; відмовостійкість; надійність; мінімальні січення; дерево відмов; беспилотный летательный аппарат; навигационно-вычислительная система; оценка риска эксплуатации; отказоустойчивость; надежность минимальные сечения; дерево отказов; unmanned aerial vehicle; onboard computing-navigational system; risk assessment; fault-tolerance; reliability; minimum cut sets; fault tree